2019
DOI: 10.1128/aac.01454-19
|View full text |Cite
|
Sign up to set email alerts
|

Conjugative Delivery of CRISPR-Cas9 for the Selective Depletion of Antibiotic-Resistant Enterococci

Abstract: The innovation of new therapies to combat multidrug-resistant (MDR) bacteria is being outpaced by the continued rise of MDR bacterial infections. Of particular concern are hospital-acquired infections (HAIs) that are recalcitrant to antibiotic therapies. The Gram-positive intestinal pathobiont Enterococcus faecalis is associated with HAIs, and some strains are MDR. Therefore, novel strategies to control E. faecalis populations are needed. We previously characterized an E. faecalis type II CRISPR-Cas system and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 57 publications
2
80
0
1
Order By: Relevance
“…There is also the lack of an effective delivery system for CRISPR/Cas9 systems, limited to phage based CRISPR/Cas9 dissemination strategies, with a risk of recombination of drug resistance genes, a narrow host range, diffusion barriers and bacterial resistance to phages [ 100 , 101 ]. Recently, bacterial conjugation seems to be one of the ways to release CRISPR/Cas9 into bacteria through the construction of a host-independent conjugated plasmid, which has effectively and selectively eliminated antibiotic resistance genes in E. faecalis [ 102 ]. Some recent original work provides a convincing demonstration of the potential of CRISPR/Cas technology to overcome the problem of multi-drug resistance, by demonstrating that existing bacterial CRISPR/Cas systems can limit the spread of drug resistance genes by countering multiple horizontal gene transfer pathways [ 103 ].…”
Section: Exploitation Of Colistin Resistance: Methods and Challengmentioning
confidence: 99%
“…There is also the lack of an effective delivery system for CRISPR/Cas9 systems, limited to phage based CRISPR/Cas9 dissemination strategies, with a risk of recombination of drug resistance genes, a narrow host range, diffusion barriers and bacterial resistance to phages [ 100 , 101 ]. Recently, bacterial conjugation seems to be one of the ways to release CRISPR/Cas9 into bacteria through the construction of a host-independent conjugated plasmid, which has effectively and selectively eliminated antibiotic resistance genes in E. faecalis [ 102 ]. Some recent original work provides a convincing demonstration of the potential of CRISPR/Cas technology to overcome the problem of multi-drug resistance, by demonstrating that existing bacterial CRISPR/Cas systems can limit the spread of drug resistance genes by countering multiple horizontal gene transfer pathways [ 103 ].…”
Section: Exploitation Of Colistin Resistance: Methods and Challengmentioning
confidence: 99%
“…In other words, guide RNAs can be designed to target virulence or antibiotic resistance genes that are specific to antimicrobial-resistant bacteria. Thus, the CRISPR-Cas9 system can be employed to neutralize antibiotic resistance genes in the targeted bacterial population without killing the beneficial bacteria in wild-type populations [ 43 , 44 , 45 , 46 ] ( Figure 3 ). For example, the CRISPR-Cas9 system is being developed to restore the sensitivity to antibiotics in extend-spectrum beta-lactamase (ESBL)-producing Escherichia coli by identifying a conserved target sequence in >1000 ESBL mutants [ 44 ].…”
Section: Crispr-cas System and Antibiotic Resistancementioning
confidence: 99%
“…In Staphylococcus aureus , phagemid-mediated delivery of CRISPR-Cas9 was used to eliminate virulence genes and antibiotic resistance genes, thereby resensitizing bacteria to antibiotics [ 43 ]. In a recent study, Rodrigues et al engineered conjugative plasmid pPD1 with a complete, constitutively expressed CRISPR-Cas9 targeting cassette that efficiently transfers to Enterococcus faecalis for the selective removal of ermB (encoding erythromycin resistance) and tetM (encoding tetracycline resistance) [ 46 ]. In vivo results showed that these transformants significantly reduced the prevalence of antibiotic-resistant intestinal E. faecalis and are immune to the uptake of antibiotic resistance determinants.…”
Section: Crispr-cas System and Antibiotic Resistancementioning
confidence: 99%
“…Therefore, TAPs appear appropriate to target a range of clinically relevant pathogenic or resistant Gram-negative bacteria ( E. coli , Citrobacter , Enterobacter , Klebsiella , Salmonella , Yersinia , Shigella , Serratia ,etc.). Recently, the narrow host range pPD1 plasmid has also been used to transfer CRISPR/Cas systems to the Gram-positive Enterococcus faecalis ( 44 ). Other reported antibacterial ( 7 , 11 ) or anti-drug ( 8–10 ) methodology using conjugation are mostly based on the incP RK2 conjugative system, which offer broad-host range, but low efficiency of transfer (10 −4 –10 −5 ).…”
Section: Discussionmentioning
confidence: 99%